A response to Gatali and Wallin (2015) Bird diversity in the savanna habitats of Akagera National Park, Rwanda, in the post-war recovery period. (31st March 2017) - Hogg, James WT; Vande weghe, Gaël R
Abstract : The paper 'Bird diversity in the savanna habitats of Akagera National Park, Rwanda, in the post-war recovery period' by Gatali and Wallin ( Ostrich 86(3): 267–276, 2015) makes several claims for new species records for Akagera National Park and Rwanda. We found that Gatali and Wallin recorded several species considered very rare in Rwanda and new discoveries; these findings often contradicted the existing literature. We doubt the validity of 34 species records and we aim to demonstrate that these claims are mostly the result of misidentification or human error and consider that future researchers should use their findings with caution. Some findings around more common species may be validated through further studies and we encourage others to conduct fieldwork in Akagera National Park.